From Social Solidarity to Transactional Relations: The Transformation of the Ompangan Tradition in Marriage Celebrations Among the Madurese Muslim Community in Kubu Raya - Susi Susanti; Masuwd, Mowafg Abrahem Masuwd; Muhammad Hasan; Q. Zaman (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
The practice of gift-giving during marriage celebrations has long served as an expression of social solidarity deeply embedded within the Madurese Muslim community. However, evolving social, economic, and cultural dynamics have driven a significant shift in the values underpinning this practice, particularly in the context of the ompangan tradition. Critical studies examining the transformation of this tradition—from a voluntary act of giving to a reciprocal obligation accompanied by social sanctions—remain scarce. This article seeks to address this gap by exploring the shifting values within the ompangan tradition among the Madurese Muslim community in Sui Kakap Subdistrict through empirical research employing a socio-legal approach. Data collection was conducted through participant observation and structured interviews with seven key informants. The findings indicate that the ompangan tradition has undergone a transformation from an affective and tradition-based social act into one characterized by rational-instrumental actions. This transformation is marked by systematic record-keeping, rigid expectations of repayment, and the imposition of social sanctions through stigmatization. Normatively, the practice of ompangan has shifted from being understood as a hibah (gift) to resembling a qarḍ (loan) due to the community’s heightened expectations of repayment. The article argues that the process of adatisation of transactional norms, which blurs the boundaries between social solidarity and economic relations, carries significant implications for the intensification of social inequalities and symbolic segregation within the community. Consequently, this study recommends strengthening customary law frameworks that are more adaptive and participatory to redirect the transformation of ompangan practices toward the principles of mutual assistance in line with the objectives of Islamic law (maqāṣid al-sharī‘ah) within the context of Islamic marriage celebrations. [Tradisi pemberian hadiah dalam perayaan pernikahan merupakan ekspresi solidaritas sosial yang telah mengakar dalam komunitas Muslim Madura. Namun, dinamika sosial, ekonomi, dan budaya yang berkembang telah mendorong pergeseran nilai dalam praktik tersebut, khususnya dalam tradisi ompangan. Kajian kritis yang menelaah transformasi makna dari pemberian sukarela menjadi kewajiban timbal balik yang disertai sanksi sosial masih sangat terbatas. Artikel ini bertujuan mengisi kekosongan tersebut dengan menelaah pergeseran nilai dalam tradisi ompangan di komunitas Muslim Madura di Kecamatan Sui Kakap, melalui penelitian lapangan dengan pendekatan sosio-legal. Pengumpulan data dilakukan melalui observasi partisipatif dan wawancara terstruktur dengan tujuh informan kunci. Temuan menunjukkan bahwa tradisi ompangan telah mengalami transformasi dari tindakan sosial berbasis nilai afektif dan tradisional menjadi tindakan yang lebih rasional-instrumental, ditandai dengan pencatatan sistematis, kewajiban pengembalian yang rigid, serta pemberlakuan sanksi sosial berbasis stigma. Secara normatif, tradisi ompangan bergeser dari akad hibah (pemberian) menjadi akad qarḍ (hutang-piutang) akibat ekspektasi pengembalian yang menguat di masyarakat. Artikel ini berargumentasi bahwa proses adatisasi norma transaksional yang mengaburkan batas antara solidaritas sosial dan relasi ekonomi berimplikasi terhadap penguatan potensi ketimpangan sosial dan segregasi simbolik dalam komunitas. Oleh karena itu, studi ini merekomendasikan penguatan hukum adat yang lebih adaptif dan partisipatif agar transformasi tradisi ompangan dapat diarahkan kembali pada prinsip tolong-menolong yang sesuai dengan tujuan hukum Islam (maqāṣid al-sharī‘ah) dalam perayaan perkawinan Islam.]